Nutrient deficiency effects on root architecture and root-to-shoot ratio in arable crops - Lopez, Gina; Ahmadi, Seyed Hamid; Amelung, Wulf; Athmann, Miriam; Ewert, Frank; Gaiser, Thomas; Gocke, Martina I.; Kautz, Timo; Postma, Johannes; Rachmilevitch, Shimon; Schaaf, Gabriel; Schnepf, Andrea; et al. (Frontiers in Plant Science, 2023)
Plant root traits play a crucial role in resource acquisition and crop performance when soil nutrient availability is low. However, the respective trait responses are complex, particularly at the field scale, and poorly understood due to difficulties in root phenotyping monitoring, inaccurate sampling, and environmental conditions. Here, we conducted a systematic review and meta-analysis of 50 field studies to identify the effects of nitrogen (N), phosphorous (P), or potassium (K) deficiencies on the root systems of common crops. Root length and biomass were generally reduced, while root length per shoot biomass was enhanced under N and P deficiency. Root length decreased by 9% under N deficiency and 14% under P deficiency, while root biomass was reduced by 7% in N-deficient and 25% in P-deficient soils. Root length per shoot biomass increased by 33% in N deficient and 51% in P deficient soils. The root-to-shoot ratio was often enhanced (44%) under N-poor conditions, but no consistent response of the root-to-shoot ratio to P-deficiency was found. Only a few K-deficiency studies suited our approach and, in those cases, no differences in morphological traits were reported. We encountered the following drawbacks when performing this analysis: limited number of root traits investigated at field scale, differences in the timing and severity of nutrient deficiencies, missing data (e.g., soil nutrient status and time of stress), and the impact of other conditions in the field. Nevertheless, our analysis indicates that, in general, nutrient deficiencies increased the root-length-to-shoot-length ratios of crops, with impacts increasing in the order deficient N > deficient P > deficient K. Our review also resolved inconsistencies that were often found in the individual field experiments, and led to a better understanding of the physiological mechanisms underlying root plasticity in low nutrient fields.